2011
DOI: 10.17221/443/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of different soil tillage systems on maize (Zea mays L.) yields

Abstract: The effects of three tillage systems: no-tillage (NT), reduced tillage (RT) and conventional tillage (CT), and three levels of fertilization (0, 258 and 516 kg/ha NPK (58:18:24)), on the maize yield during ten years (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) were analyzed on the chernozem soil type in Zemun Polje, Serbia. Statistical analyses showed significant effects of all three factors i.e., year, soil tillage and amount of fertilizers, and their interactions on the maize yield. The ten-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Several authors point to large variations of grain yields during the first years after setting up soil conservation technologies, as a result of both the adaptation to the soil properties and variations of the weather conditions. Significant effects of the year on the yield are widely documented in long-term field studies (Šíp et al 2009, Videnovič et al 2011). Lahmar (2010 summarized the results of the KASSA project, which showed that within Europe conservation agriculture does not necessarily generate increases in yields.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors point to large variations of grain yields during the first years after setting up soil conservation technologies, as a result of both the adaptation to the soil properties and variations of the weather conditions. Significant effects of the year on the yield are widely documented in long-term field studies (Šíp et al 2009, Videnovič et al 2011). Lahmar (2010 summarized the results of the KASSA project, which showed that within Europe conservation agriculture does not necessarily generate increases in yields.…”
Section: Resultsmentioning
confidence: 99%
“…Groundnut (Arachis hypogaea L), also known as "peanut" or "earthnuts" is referred to a king of "oil seeds" and globally cultivated on an area of 24.62 million hectares of land (FAO, 2013). Yields obtained from the two crops when grown as sole crop or when they are intercropped are low due to poor soil fertility and inadequate field management by farmers (Videnovic et al, 2011;Howell, 2011;Patil et al, 2015). The reason for the low yields is because the humid tropics are characterized by highly erosive, erratic and poorly distributed rains (Lal, 1980;Osunbitan et al, 2005;FAO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Only in conventional tillage the differences between the fertilization levels were evident with F1 and to some extent F2 fertilization levels, highlighting them as levels that could increase yields in the highest extent. In parallel, Videnović et al (2011) also revealed the benefits of conventional tillage under rain-fed conditions, irrespective of the level of applied fertilizer. CONCLUSIONS According to the obtained results, it could be concluded that irrigation diminished the negative influence of environmental factors on maize grain yield.…”
Section: Resultsmentioning
confidence: 89%
“…Different studies concerning variations in cropping measures (tillage practices, fertilization amounts and rates) indicated that under rain-fed conditions on chernozem, conventional tillage is the best practice to lower energy inputs and increase maize yield (Videnović et al, 2011). Moreover, increased amounts of fertilizer could compensate yield deprivations arising from reducing some tillage operations (Tolimir et al, 2001).…”
Section: Introductionmentioning
confidence: 99%